2015
DOI: 10.1186/s13287-015-0152-8
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo identification and characterization of a population of CD13high CD105+ CD45− mesenchymal stem cells in human bone marrow

Abstract: IntroductionMesenchymal stem cells (MSCs) are multipotent cells capable of self-renewal and multilineage differentiation. Their multipotential capacity and immunomodulatory properties have led to an increasing interest in their biological properties and therapeutic applications. Currently, the definition of MSCs relies on a combination of phenotypic, morphological and functional characteristics which are typically evaluated upon in vitro expansion, a process that may ultimately lead to modulation of the immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 50 publications
4
15
0
Order By: Relevance
“…39 These results are in line with recent observations by Nemeth et al who described the presence of abnormal MSCs with slow proliferation, signs of senescence, and impaired osteogenic function (vs normal MSC colonies) in SM patients. 60 Of note, these authors did not find the KIT D816V mutation in cultured BM MSCs from any of the 5 SM patients they analyzed.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…39 These results are in line with recent observations by Nemeth et al who described the presence of abnormal MSCs with slow proliferation, signs of senescence, and impaired osteogenic function (vs normal MSC colonies) in SM patients. 60 Of note, these authors did not find the KIT D816V mutation in cultured BM MSCs from any of the 5 SM patients they analyzed.…”
Section: Discussionsupporting
confidence: 91%
“…2 BM cells showed immunophenotypic features which were fully consistent with previously defined criteria for MSCs [39][40][41] such as: absence of CD11b, CD14, CD19, CD34, and CD45 expression; heterogeneous reactivity for CD10 and HLA-DR; and expression of the CD44, CD73, CD90, CD105, CD140b, CD146, CD271, MSCA-1, SSEA-4, and STRO-1 MSC-associated markers (supplemental Figure 1, available on the Blood Web site).…”
Section: Resultssupporting
confidence: 75%
“…Rasini et al, 2013 reported site-specific phenotypes based on cell-surface marker expression between cells in different anatomical localizations [16]. Previous studies focused on characterizing individual BMSC populations in human bone marrow within the freshly isolated MNC fraction: CD45 low /D7FIB+/CD271+ [11]; lin−/CD271+/CD45−/CD146+ [17]; CD64 bright /CD31 bright /CD14 neg [18]; CD13 high /CD105+/CD45− [19]; CD145−/CD34−/CD146+ [20,21,22]; PDPN+/CD146−CD73+CD164+ [23]. Whether the abundance of these discrete BMSC subsets may determine the yield and/or the phenotypic characteristics of the subsequently in vitro derived stromal population remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…These surface markers are used to purify BM-MSCs by fluorescence-activated cell sorting (FACS) as well as the magnetic-activated cell sorting (MACS). In addition, the use of Percoll gradient centrifugation and adherence to tissue-culture treated plastics are proposed as more simple techniques to purify BM-MSCs [163]. BM-MSCs can be used as undifferentiated or fully differentiated cells for TE applications.…”
Section: Bone Marrow Stem Cells (Bm-mscs)mentioning
confidence: 99%